Thermal stability of B2 CuZr phase, microstructural evolution and martensitic transformation in Cu–Zr–Ti alloys. (December 2015) - Song, K.K.; Wu, D.Y.; Pauly, S.; Peng, C.X.; Wang, L.; Eckert, J.
Abstract: The effects of minor Ti addition on the thermal stability of B2 CuZr phase, the microstructure and the martensitic transformation (MT) in Cu50 Zr50−x Tix (x = 0, 2.5, 7.5 and 10 at%) alloys were investigated. It was found that the crystallization products, i.e. Cu10 Zr7 and Cu(Ti, Zr)2, of Cu–Zr–Ti amorphous alloys transform to B2 CuZr phase at high temperatures. The corresponding eutectoid transformation temperature gradually increases with increasing Ti content, implying the decrease of the thermodynamic stability of the B2 CuZr phase. The microstructures of Cu–Zr–Ti martensitic alloys were proven to contain B2 CuZr, CuZr martensite, Cu10 Zr7, Cu(Ti, Zr)2, and ZrTiCu2 crystals. Dilatometric measurements reveal that the MT temperature reduces with increasing Ti content, which would be of electronic nature. With increasing thermal cycles, the MT temperature gradually decreases while the reverse MT temperature increases, which results from the enhancement of the dislocation density, the partial decomposition of the equiatomic CuZr crystals and the partially reversible MT. Highlights: Thermal stability of B2 CuZr phase was studied in CuZrTi alloys. Microstructures of CuZrTi martensitic alloys were checked. Martensitic transformation temperature decreases with increasing Ti content. Martensitic transformation in CuZr-based alloys could be of electronic nature. Effects of thermal cycling on martensitic transformation behaviors were discussed.